2017
DOI: 10.1016/j.cattod.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and crystal structure of tetraoctylphosphonium tetrakis(pentafluorophenyl)borate ionic liquid for electrochemistry at its interface with water

Abstract: With ongoing and expending global energy needs, nuclear power is likely to be a key energy source for many more generations. A key question is still the fate of spent nuclear fuel (SNF). SNF contains a great deal of valuable material. In order to improve safety and handling, herein is proposed relatively high melting point ionic liquid (IL) or organic ionic plastic crystals (OIPCs) for biphasic water|IL metal ion extraction. The proposed IL, tetraoctylphosphonium tetrakis(pentafluorophenyl)borate, P8888(C6F5)4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…1A). The PPW is 400mV wide and in good agreement with previous results [60][61][62], but is small compared to ILs incorporating fluorinated phenyl borate anions [18,56,58,63,64]. The lower viscosity of P66614NTf2, however, makes it easier to manipulate at ambient temperature (~330mPa s, [65,66]) versus more hydrophobic ILs [18,54,56,58,63,64].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…1A). The PPW is 400mV wide and in good agreement with previous results [60][61][62], but is small compared to ILs incorporating fluorinated phenyl borate anions [18,56,58,63,64]. The lower viscosity of P66614NTf2, however, makes it easier to manipulate at ambient temperature (~330mPa s, [65,66]) versus more hydrophobic ILs [18,54,56,58,63,64].…”
Section: Resultssupporting
confidence: 87%
“…It is then suggested that solutions of LiBH4 in P66614NTf2 can be used to deliver H2 at reasonable rates; similar results are expected for LiBH4 in P8888Br, an organic ionic plastic crystal (OIPC) [18]. In a typical GC column experiment, 0.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, ionic-liquid membranes have been suggested as effective media for the separation of volatile organic compounds at the air-liquid interface. Other recent work in this area also explore the possibility of using hydrophobic ILs in electrochemical applications and metal ion extractions [10,11] The knowledge of the structure and packing of ionic liquids at an interface is therefore of utmost importance for the rational design of such media. A key aspect in the design and preparation of functional materials is the control of intermolecular interactions and molecular packing in the first few monolayers at the surface [7].…”
Section: Introductionmentioning
confidence: 99%